Vision of Prime Minister of India: Building Smart City To Uphold Economy - Singh, Zigyasa; Singh, Dr. Dhrmadev (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The developed cities are a mirror of a developed economy that reveals the high lifestyle of that country because the cities are the engines of development of the economy of each nation (including India). About 31.2 percent of India's current population lives in urban areas and they contribute 63 percent to India's GDP. It is estimated that by increasing the urbanization, 40 percent of the Indian population will occupy cities in the year 2030 and it will contribute 75 percent to the gross domestic product. For this broad development of physical, institutional, social and economic infrastructure is expected. Development of all these is important in establishing a best cycle of development and progress to improve the quality of life and attract common mass and investment to the cities. Keywords: GDP, Smart Cities, Economic Development. Financial Strategies